The Scottish Council for Research in Education. Fiftieth Annual Report 1977-78 - Scottish Council for Research in Education; Scottish Council for Research in Education ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This annual report of the Scottish Council for Research in Education provides: (1) a list of officers, members and officials; (2) reports of council and committees; (3) reports on projects; (4) reports on liaison with other organizations, papers delivered, and consultative services undertaken by the Council's staff; (5) a report of the organization's finances and accounts; (6) a list of research papers in education and educational psychology presented for degrees in Scottish universities in 1977; and (7) a list of currently available Council publications. (DS)
Availability: The Scottish Council for Research in Education, 16 Moray Place, Edinburgh EH3 6DR, Scotland (free).
ERIC Note: Some small print marginally legible.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annual Reports; Educational Research; Foreign Countries; Professional Associations; Research Projects; Scotland -- Scottish Council for Research in Education; Reports, Descriptive